(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article focuses on the ideas of the Renaissance period, in which it is noted that it is possible to direct people to happiness through the system of power, to coordinate the relations between society and the state with the help of science and good morals.